Adam Smith in a warmer world: climate change, multilateral trade and national food security. (1st September 2014) - Crump, Larry
Abstract : Market efficiency is essential in a world of scarce resources, but it is a secondary concern if human survival depends on a market that can provide reliable agricultural supply. For example, the projected increase in the frequency, magnitude and severity of extreme weather events (as increasing CO2 emissions make the world warmer) has profound implications for the reliability of the multilateral agricultural market. Market reliability is assumed to be embedded in supply and demand price transmission, although this assumption may not hold in a changing climate. This paper examines these concerns and makes recommendations to the World Trade Organization (WTO) and to leaders of national governments about rethinking the balance between interdependence on a multilateral agricultural market and national independence (not self-sufficiency) based on development of multiple food delivery systems to protect against periodic agricultural price shocks. Once established, via the WTO Doha round, a non-distorted multilateral agriculture market will become the primary global food security system, but national governments may also wish to examine a range of secondary food security systems.